Java 7: A Beginner's Tutorial - Kurniawan, Budi (Brainy Software Inc, 2011)
A Books24x7's TOP 10 title for 4 consecutive years! Java is an easy language to learn. However, you need to master more than the language syntax to be a professional Java programmer. For one, object-oriented programming (OOP) skill is key to developing robust and effective Java applications. In addition, knowing how to use the vast collection of libraries makes development more rapid. This book introduces you to important programming concepts and teaches how to use the Java core libraries. It is a guide to building real-world applications, both desktop and Web-based. The coverage is the most comprehensive you can find in a beginner's book. Here are some of the topics in this book: - Java language syntax - Object-oriented programming - The Collections Framework - Working with numbers and dates - Error handling - Input Output - Generics - Annotations - Swing - Database access - Internationalization - Networking - Applets - Multithreading and the Concurrency Utilities - Servlet and JavaServer Pages - API documentation - Security - Application deployment This book covers Java SE 7 and was written with clarity and readability in mind. Print length: 716 pages.